INDIKATOR KINERJA TELEKOMUNIKASI DALAM PEMANFAATAN MENARA SELULER BERSAMA - Paronda, Abdul Hafid (JREC (Journal of Electrical and Electronics), 2012)
Enhancement of mobile cellular subscribers number need amount of cell site within it BTS supportingsystem. It face on government policy that arrange the utilizing of the cellular common tower in order tomaintain the esthetical planology city management. Telecommunication performance system tend tochange down as impact of telecommunication operator co-existence on cellular common tower andsubscribers intensity around the cell site.Keywords : Telecommunication performance, common cellular tower, esthetical city management